The Influence of Rewards and Punishment on the Performance of Employees in Industrial Sector Companies - Rendragraha, Nadhif Dwi; Suwaji, Rifki (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Employee performance is a fundamental basis for improving company productivity. Advancing a company requires not only adequate facilities, sophisticated technology, and smooth financial systems, but also high-quality human resources through the implementation of rewards and punishments. Therefore, this research was conducted to determine how rewards and punishments partially and simultaneously affect employee performance and whether any of these independent variables have a dominant influence on employee performance at CV. Rizki Alam Jaya, Sidoarjo Branch. Data collection methods included questionnaires, field studies, and literature studies, with a sample of 40 employees. A quantitative approach was used, and the data were analyzed using SPSS 20 software. The results from the t-test showed that the reward variable has a partial impact on employee performance, as does the punishment variable. Based on the highest value, the reward variable has a dominant impact on employee performance. Meanwhile, according to the F-test, the reward and punishment variables have a simultaneous impact on employee performance.